2022
DOI: 10.5826/dpc.1203a130
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoscopy in the Diagnostics of Incontinentia Pigmenti Skin Lesions

Abstract: Introduction: Incontinentia pigmenti (IP) is a rare X-linked geno-dermatosis characterized by numerous findings. Skin biopsy and histopathological analysis are considered as minor criteria for the diagnosis of IP. We assume that dermoscopy can assist the earlier diagnosis of IP. Objectives: To gain experience in earlier diagnosis of IP by observing dermoscopic findings of cutaneous changes. Methods: We revised confirmed cases of IP and examined them using dermoscopy, comparing histopathological and dermoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the other hand, dermoscopy can be a useful diagnostic tool in cutaneous lesions of IP. On dermoscopic findings in the pigment stage of IP, Bishnoi et al reported linear brown to grey-brown dots ( 10 , 11 ) and Minic et al showed linear grey to grey-brown dots on the light-brown pigmented background that intermingled with normal skin and perifollicular depigmentation ( 14 ). Similarly, we showed linear distributed grey-brown dots on the brown pigmented background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, dermoscopy can be a useful diagnostic tool in cutaneous lesions of IP. On dermoscopic findings in the pigment stage of IP, Bishnoi et al reported linear brown to grey-brown dots ( 10 , 11 ) and Minic et al showed linear grey to grey-brown dots on the light-brown pigmented background that intermingled with normal skin and perifollicular depigmentation ( 14 ). Similarly, we showed linear distributed grey-brown dots on the brown pigmented background.…”
Section: Discussionmentioning
confidence: 99%
“…Blaschkoid-distributed hyperpigmented lesions include linear and whorled nevoid hypermelanosis, hypomelanosis of Ito, and lichen planus pigmentosus, and may be confused with stage III of IP (12)(13)(14). On the other hand, dermoscopy can be a useful diagnostic tool in cutaneous lesions of IP.…”
Section: Discussionmentioning
confidence: 99%